Occupational asthma from reactivity to an alkaline hydrolysis derivative of gluten - Lachance, Paul; Cartier, Andre; Dolovich, Jerry; Malo, Jean-Luc (Journal of allergy and clinical immunology, 1988)
A 29-year-old female subject had been working for 13 years in a company producing biscuits. She was exposed intermittently to an alkaline hydrolysis wheat gluten derivative (AHGD) that was incorporated into marshmallows. Five years before being referred, she started reporting rhinoconjunctivitis and asthmatic symptoms immediately after handling AHGD. When she was first assessed, she had avoided contact with AHGD for 1 year, and she was asymptomatic. Normal spirometry and bronchial responsiveness to histamine (provocative concentration causing a 20% fall in FEV 1, 22 mg/ml) were obtained. There was a positive allergy skin test to ragweed pollen and to AHGD at 0.01 mg/ml. Skin tests with individual extracts of cereals, including wheat, were negative. Inhalation challenge with AHGD for 15 seconds caused immediate rhinoconjunctivitis and bronchoconstriction (maximum fall of 40% in FEV 1 30 minutes after the exposure) with complete recovery 2 hours later. There was no reaction thereafter, and the provocative concentration of histamine causing a 20% fall in FEV 1 was not significantly-changed (13.1 mg/ml) 9 hours after the challenge. Inhalation challenge with wheat flour containing native gluten for 30 minutes did not cause any symptoms or significant change in FEV 1. IgE RAST counts were greater with the AHGD than with gluten and the whole wheat extract; the opposite was generally found with sera from individuals with baker's asthma and wheat food allergy. With the serum of the affected worker, AHGD completely inhibited the corresponding RAST, but gluten did not. With wheat food allergy, AHGD was relatively inactive in hibition of the wheat and gluten RAST, but gluten was effective. This is the first account of occupational asthma and immunologic reactivity caused by AHGD. This article illustrates the principle of immunologic reactivity dependent on alteration of a food component (gluten) with resulting emergence or expression of new antigenic determinants.